Link between procrastination and academic stress in 5th year high school students from an educational institutionin El Milagro - Luján Vásquez, Fiorella Lizeth; Mendoza Garcia, Victor Manuel; Figueroa Polo, Jose Francisco; Mauricio Aguilar, Brayan Scott; Neyra Fasabi, Andrea Solange; Woolcott Chumpitaz, Carlos Alfredo; Tantaleán Pérez, Magali Roxana (LACCEI, 2025)
Abstract– This research aims to identify the relationshipbetween procrastination and academic stress in 5th-year secondaryschool students from an educational institution in El Milagro, withthe hypothesis of a positive correlation between both variables. Thestudy aligns with Sustainable Development Goal (SDG) 4: "QualityEducation." A quantitative approach and correlational design wereused, with a sample of 26 students selected through non-probabilityconvenience sampling. The instruments were digital surveys withthe validated EPA and SISCO IV questionnaires, and the data wereanalyzed in SPSS using normality tests and Pearson correlation.The results indicated that 88.5% of the students had a moderatelevel of academic stress, and 69.2% had a medium level ofprocrastination. The correlation between both variables was weak(p=0.183), suggesting that there is no significant relationship in thispopulation. In conclusion, although both phenomena are common,they are not directly related, highlighting the need for strategies toimprove time management and emotional well-being